Efficacy Of Triamcinolone Injection In Management Of Oral Lichen Planus - Humera Iqbal; Uzair Luqman; Kanwal Zulfiqar; Zarnab Rizwan; Mobina Fatima Zulfiqar (Journal of Rawalpindi Medical College)
Objective: To study the efficacy of triamcinolone injection in the treatment of oral lichen planus patients presented to the department of oral and maxillofacial surgery at KRL General Hospital Islamabad.